2013
DOI: 10.4236/oji.2013.32008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family history and consanguinity in primary immunodeficiency diseases in children in Qatar

Abstract: Background: The high consanguinity in Middle East increases the risk of genetic diseases, including primary immunodeficiency diseases (PIDConclusions: This study indicates that family history is common in children with PID and helpful in reducing the delay age. Consanguinity among families of affected children is also high (higher than healthy population). Paternal parallel cousin marriages are the most common type of consanguinity. For a practicing physician, family history is a simple and useful tool when su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…The most common diagnostic criteria were based on The European Society for Immunodeficiencies (ESID) and The International Union of Immunological Societies (IUIS) .…”
Section: Resultsmentioning
confidence: 99%
“…The most common diagnostic criteria were based on The European Society for Immunodeficiencies (ESID) and The International Union of Immunological Societies (IUIS) .…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, the total of Qatar population reached 2,123,160 of whom 302,313 are children younger than 14 years [28]. The frequency of AT in Qatar is estimated to be 1 per 16,796 live births, still higher than reported in other regions of the world (in 40,000 to 100,000 people worldwide) [29], and due to high consanguinity rate among primary immunodeficiency diseases in Qatar [30]. Although our study revealed a correlation between clinical severity scales and cerebellar atrophy scores, a larger sample size most likely would have shown a statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…PIDs are acquired by different modes of inheritance [ 4 ]. Communities with a common practice of consanguinity, such as Iran, Saudi Arabia, Turkey, Morocco, Egypt, Kuwait, and Oman, have a high rate of PIDs [ 3 ]. In addition, autosomal recessive inheritance is not the only culprit in consanguineous marriage, but multifactorial factors play a role as well [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of PID is crucial because often lifesaving interventions can be provided to decrease the rate of morbidity and mortality [ 2 ]. A major proportion of affected infants and children are offspring of consanguineous marriage; in addition, family medical history is very common in PID and it is an essential component in the diagnosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%